Adição de kisspeptina no meio de fertilização in vitro de embriões bovinos - Cardoso, Graciele Freitas (2018)
The aim was to evaluate the different concentrations of Kisspeptin (Kp) and its effect in the process of in vitro fertilization of bovine embryos about the quality and production rates. In Experiment 1 the minimum concentration of Kp was determined to be used at medium FIV, starting from the treatments: control (n=240); Kp 10-5 M (n=223); Kp 10-6 M (n=225) and Kp 10-7 M (n=245). In Experiment 2, the oocytes were distributed in four treatments: control (n=362); Kp 10-1 M (n=425), Kp 10-7 M (n=304), and antagonist P234 4x10-6 M (n=424). The sperms were enabled by Percoll® discontinuous gradient, and coincubated with the oocytes from 16 to 18 hours in stove culture at 38.5°C with 5% of CO2. After this period, the zygotes were incubated in Synthetic Oviduct Fluid (SOF) during 7 days in the same conditions. The rate of cleavage was evaluated 48 hours after fertilization and the rate of blastocysts and development stage/quality on the seventh day. A numerical score was adopted from 1 to 4 for evaluation of the development stage, as 1 corresponds to initial blastocyst, 2 blastocyst, 3 expanded blastocyst and 4 hatched blastocyst. The quality was evaluated by 3D confocal microscopy, and the analyzed data by PROC GLIMMIX/SAS and Kruskal-Wallis test. In Experiment 1, there wasn’t difference between the treatments rates of cleavage and blastocysts respectively: control (82,0%/34,2%); Kp 10-5 M (81,6%/26,9%); Kp 10-6 M (80,8%/29,3%) and Kp 10-7 M (80,8%/29,4%) (P > 0,05). In Experiment 2, the averages from the rates of cleavage and blastocysts were similar between the treatments: control (85,1%/38,1%), Kp 10-1 M (82,6%/33,6%), Kp 10-7 M (83,6%/34,9%) and P234 (81,4%/31,6%) (P > 0,05). A total of 514 embryos were produced, with the following averages of development score: control 2,89; Kp 10-1 M 3,04; Kp 10-7 M 2,79 and P234 2,63, without statistical difference among them (P > 0,05). About the quality, 360 embryos were evaluated, n=30/treatment/coloring. The parameters observed were production of reactive oxygen species (ROS), necrosis, apoptosis and mitochondrial potential. Each embryo supplied from 3 to 8 images (n=1.492) with fluorescence intensity in pixels. The control group presented bigger percentage of ROS: control 3,76%; Kp 10-1 M 0,25%; Kp 10-7 M 2,95% and P234 0,91% (P < 0,05). The percentage of cellular degeneration was similar between the treatments: control 1,51%; Kp 10-1 M 1,73%; Kp 10-7 M 4,71% and P234 1,98% (P > 0,05). The average of apoptosis was similar between the treatments: control 2,79%; Kp 10-7 M 1,67% and P234 6,11% (P > 0,05). The mitochondrial potential had bigger percentage in the group P234: control 0,51%; Kp 10-1 M 0,26%; Kp 10-7 M 0,22% and P234 1,43% (P < 0,05). The addition of kp-10 amid fertilization didn’t interfere in the rates of cleavage and blastocyst, as well as in the embryonic development stage. The Kp didn’t have effect in the apoptosis, necrosis, nor even in the mitochondrial potential. On the other hand, the Kp decreased the intracellular levels of ROS, suggesting its involvement in the antioxidant control.